Shared Power, Risk-taking, and Innovation: Participatory Action Research in Jewish Education. Issue 2 (3rd April 2019) - Raider-Roth, Miriam; Rector-Aranda, Amy; Kaiser, Tammy; Lipinsky, Liron; Weikel, Alison; Wolkenfeld, Sara; Zaidenberg, Liat
ABSTRACT: In this article, the authors describe and discuss applications of the Group-Level Assessment/Understanding (GLA/GLU) process, an innovative participatory action research methodology. The authors first describe the GLA/GLU application in the Mandel Teacher Educator Institute (MTEI) and the creation of an MTEI interpretive community to deeply analyze the collected data. The authors then describe adaptations of the process in their home communities to address community-identified dilemmas, tensions, and problems. The article concludes with reflections on common themes that emerged in the GLA/GLU applications–shared power, risk-taking, and methodological innovation.